Reactive oxygen species trigger motoneuron death in non-cell-autonomous models of ALS through activation of c-Abl signaling - Rojas, Fabiola; Gonzalez, David; Cortes, Nicole; Ampuero, Estibaliz; Hernández, Diego E.; Fritz, Elsa; Abarzua, Sebastián; Martinez, Alexis; Elorza, Alvaro A.; Alvarez, Alejandra; Court, Felipe; van Zundert, Brigitte (Frontiers in Cellular Neuroscience, 2015)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease in which pathogenesis and death of motor neurons are triggered by non-cell-autonomous mechanisms. We showed earlier that exposing primary rat spinal cord cultures to conditioned media derived from primary mouse astrocytes (ACM) that express human SOD1G93A (ACM-hSOD1G93A) quickly enhances Nav channel-mediated excitability and calcium influx, generates intracellular reactive oxygen species (ROS), and leads to death of motoneurons within days. Here we examined the role of mitochondrial dysfunction and of the activation of c-Abl, a tyrosine kinase that induces apoptosis. We show that ACM-hSOD1G93A, but not ACM-hSOD1WT, increases c-Abl activity in motoneurons, interneurons and glial cells, starting at 60 min; the c-Abl inhibitor STI571 (imatinib) prevents this ACM-hSOD1G93A-mediated motoneuron death. Interestingly, similar results were obtained with ACM derived from astrocytes expressing SOD1G86R or TDP43A315T. We further find that co-application of ACM-SOD1G93A with blockers of Nav channels (spermidine, mexiletine, or riluzole) or anti-oxidants (Trolox, esculetin, or tiron) effectively prevent c-Abl activation and motoneuron death. In addition, ACM-SOD1G93A induces alterations in the morphology of neuronal mitochondria that are related with their membrane depolarization. Finally, we find that blocking the opening of the mitochondrial permeability transition pore (mPTP) with cyclosporine A, or inhibiting mitochondrial calcium uptake with Ru360, reduces ROS production and c-Abl activation. Together, our data point to a sequence of events in which a toxic factor(s) released by ALS-expressing astrocytes rapidly induces hyper-excitability, which in turn increases calcium influx and affects mitochondrial structure and physiology. ROS production, mediated at least in part through mitochondrial alterations, trigger c-Abl signaling and lead to motoneuron death.